Integrating Local Cultural Heritage into Early Childhood Education through Role-Playing Games: A Quasi-Experimental Study on Rendang Literacy - Hasanah, Alfisa; Eliza, Delfi; Rakimahwati, Rakimahwati; Yeni, Indra (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to evaluate the effectiveness of Role Playing Game (RPG) media in enhancing Minangkabau natural cultural literacy among early childhood learners at TK Al Hidayah Tabing Padang. A quasi-experimental method employing a nonequivalent control group design was used, involving 20 children aged 5–6 years who were assigned to experimental and control groups. Data were collected through observation and analyzed using SPSS 25.0, with tests for normality, homogeneity, and independent sample t-tests. The results revealed a significant difference in cultural literacy between the experimental and control groups, with a p-value of 0.000 < 0.05 and a Cohen’s d value of 2.96, indicating a very large effect size. These findings confirm that RPG media is highly effective in promoting cultural literacy in early childhood. This study contributes to the development of culturally responsive education and suggests the integration of RPG-based learning into early childhood curricula as a practical strategy for preserving regional cultural heritage from an early age.